Computer Vision Syndrome among Students in Islamic Boarding School during COVID-19 Pandemic - Fasya, Abdul Hakim Zakkiy; Lutfiya , Indah; Sahri, Moch; Ridlo, Abdul Jabbar; Rahmawati, Adinda Triya; Pratama, Leo Dewa Lucky (TEKNOLOGI MEDIS DAN JURNAL KESEHATAN UMUM, 2023)
During the COVID-19 pandemic, computer vision syndrome (CVS) caused by the implementation of online learning was an inevitable effect. This study aimed to test the effectiveness of using the Eye Care and Eye Pro Protect Your Vision applications as a step to treat and prevent the severity of CVS. A total of 16 students who participated in virtual classroom learning (81.20% female, 87.50% laptop users with heavy duration, 93.70% experienced CVS) were included. The most frequent symptom in CVS subjects was eye pain (96.5%), while the most intense symptom was a feeling of double vision (15.9%). The use of applications can significantly reduced the duration of laptop use (p=0.025) using the Mc Nemar test. The Eye Care application reduced symptoms by 75%, while the Eye Pro was 62.5%. The Eye Care application can provide a decrease in the duration of screen time and provide rest time for better eyes. Recommendations for preventing CVS based on causal factors can be adjusted to reduce the burden of online study, increase rest time and use screen time reminder applications.